Electrical and Vibrational Studies of Na2K2Cu(MoO4)3. (11th June 2017) - Dridi, Wassim; Zid, Mohamed Faouzi; Maczka, Miroslaw
Abstract : The complex impedance of Na2 K2 Cu(MoO4 )3 material has been investigated in the temperature range of 653–753 K and in the frequency range of 40 Hz–5 MHz. Electrical behavior of the studied material is explained through an equivalent circuit model which takes into account the contributions of grains and grains boundaries. The number of vibrational modes was calculated using group theoretical approach. The infrared and Raman spectra have also been measured and vibrational assignment has been proposed.